Pooled analysis of the efficacy and safety of intraoperative dexmedetomidine on postoperative catheter‐related bladder discomfort. Issue 1 (4th June 2020) - Shi, Hongbin; Zhang, Huaping; Pan, Weizhong; Lu, Youyi; Zhang, Yong; Chen, Linjing; Wei, Chunxiao; Cui, Yuanshan
Abstract: Objectives: The goal of the pooled analysis was to demonstrate the efficacy and safety of intraoperative dexmedetomidine in postoperative catheter‐related bladder discomfort (CRBD). Methods: MEDLINE, the Cochrane Central Register of Controlled Trials, and the Excerpta Medica Database (Embase) were used to pick out randomized controlled trials (RCTs) that used intraoperative dexmedetomidine in postoperative CRBD. This study was carried out using the preferred reporting items for systematic reviews and pooled analysis. We used RevMan version 5.3.0. to analyze the data. Results: Seven RCTs involving 607 patients were brought into in the analysis. The incidence of CRBD and the incidence of moderate to severe CRBD were assessed at 0 hours, 0.5 or 1 hour, 2 or 3 hours, 6 hours, and 12 or 24 hours postoperatively. The analysis proved that both the incidence of CRBD ( P  < .00001) and the incidence of moderate to severe CRBD had a statistically significant reduction at 0 hours, 0.5 or 1 hours, 2 or 3 hours, and 6 hours postoperatively ( P  < .00001, P  <.00001, P  <.00001, P = .003, respectively). The postoperative pain score was lower in the dexmedetomidine group at 0 hours ( P  < .00001) and 1 hour ( P = .002). Safety assessments indicated that there were no statistical differences between dexmedetomidine and control for side effects, mainly including dry mouth ( P = .99) and postoperative vomiting and nausea ( P = .77). Conclusions: The pooled analysis demonstrates that intraoperative dexmedetomidine administration decreases the rate and severity of early postoperative CRBD without causing significant side effects.